2017
DOI: 10.1039/c6ra27255j
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of isolated and crystal 4,10-dinitro-2,6,8,12-tetraoxa-4,10-diazaisowurtzitane according to ab initio molecular dynamics simulations

Abstract: We performed ab initio molecular dynamics simulations to study the initiation chemical reaction and subsequent decomposition mechanism of a 4,10-dinitro-2,6,8,12-tetraoxa-4,10-diazaisowutrzitane (TEX) crystal at 2160 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…We could gather h 50 values in centimeter measured with two similar approaches: five (TNCB, TNTriCB, CL20, DINGU, and TNAZ) out of the six molecules were obtained using the ERL Type 12 tooling with 2.5 kg impact hammer protocol . The TEX molecule, which was not included in the training group (see below), had its h 50 value also measured by a drop test using similar determination parameters . We expect that this approach minimizes the inconsistency of the used h 50 values hence their analysis with our mathematical models.…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We could gather h 50 values in centimeter measured with two similar approaches: five (TNCB, TNTriCB, CL20, DINGU, and TNAZ) out of the six molecules were obtained using the ERL Type 12 tooling with 2.5 kg impact hammer protocol . The TEX molecule, which was not included in the training group (see below), had its h 50 value also measured by a drop test using similar determination parameters . We expect that this approach minimizes the inconsistency of the used h 50 values hence their analysis with our mathematical models.…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…[13,63,64] The TEX molecule, which was not included in the training group (see below), had its h 50 value also measured by a drop test using similar determination parameters. [2,[65][66][67] We expect that this approach minimizes the inconsistency of the used h 50 values hence their analysis with our mathematical models.…”
Section: On the Choice Of The Set Of Molecules And The Availabilitymentioning
confidence: 99%
“…For path (b), the C─H bond broke to release H radicals, which can catalyze the reactions of other molecules and radicals. Xiang et al [8] have ever reported that the generated H radicals are very active and can prompt other unreacted TEX molecules to decompose. This is similar to our findings of the decompositions of the cocrystal.…”
Section: Resultsmentioning
confidence: 99%
“…And these studies provide some useful information for understanding the complicated behaviors of the explosives. Xiang et al performed AIMD simulations to study the initiation mechanism and the subsequent decomposition process of the TEX crystal at 2160 K. Wu et al uncovered the thermal decomposition mechanisms of the 3,6‐di(azido)‐1,2,4,5‐tetrazine (DiAT) crystal at 3000 K. Later, Wu et al performed AIMD simulations to study coupling effects of temperature (534–873 K) and pressure (1–20 GPa) on the initiation mechanisms and subsequent chemical decompositions of nitramine explosive HMX. Xiang et al used the AIMD method to investigate initial decomposition mechanisms and subsequent chemical processes of β‐HMX crystals at high temperature coupled with high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical decomposition mechanism, kinetic parameters and thermodynamic properties are the key factors in understanding ignition and combustion process and product distribution during explosion . In the present study, isoconversional kinetic analysis methods are used to explore the kinetics of the multistep thermal decomposition .…”
Section: Introductionmentioning
confidence: 99%